Incidencia de la organización social en el desarrollo comunitario del sitio San Vicente del Jobo, periodo 2022-2023 - Paladines Salamea, Kevin Joel; Sizalima Becerra, Jacqueline Gisell (Machala: Universidad Técnica de Machala, 2023)
The present degree work Incidence of social organization in the community development of the San Vicente del Jobo site, period 2022-2023 seeks to understand, analyze and relate through the bibliographic review of scientific articles and through the research that was carried out in- situ territory through the survey technique, the importance of social organizations in the development of the community. In its context, it was possible to corroborate that although there are many neighborhood organizations on the site, they are not fulfilling their role or function to achieve progress and improve the quality of life of people through the execution of works working in coordination with the competent authorities of the GADM of Arenillas. For this reason, the general objective of the research focuses on Determining the impact of social organization on the community development of the San Vicente del Jobo Site. Likewise, the research work is based on the Sociological Structural Functionalism Theory of Emeli Durkheim since social organizations are related to society and its structures that function thanks to the roles played by each individual from their respective status, therefore, achieve progress and social development. The methodological approach applied in the research is quantitative, which contributes to a more systematized work in obtaining true information. Likewise, information was collected through the survey technique in order to explain and analyze the data obtained, which I facilitate. a more precise and clear interpretation. Based on the results obtained, it can be stated that they exist; internal social problems on the site, the existing social organizations are weakened and are not fulfilling their function correctly, according to the data they reflect that there are individual interests in the directive and they are of a lucrative and economic nature and their acceptance of it is low, In addition, the quality of life of the inhabitants is low and there are ideological differences between political parties and movements in times of campaigns, all these problems are negatively affecting and hindering the community development of the site and affecting the quality of life of the inhabitants. delaying the execution of works for the benefit of the population, based on the aforementioned, the problem under study must be addressed immediately by strengthening the community and leadership, empowering it and committing both the residents and the cantonal authorities with the purpose of achieve collective well-being.
El presente trabajo de titulación Incidencia de la organización social en el desarrollo comunitario del sitio San Vicente del Jobo, periodo 2022-2023 busca entender, analizar y relacionar mediante la revisión bibliográfica de artículos científicos y a través de la investigación que se realizó in-situ territorio por medio de la técnica de la encuesta, la importancia de las organizaciones sociales en el desarrollo de la comunidad. En su contexto, se pudo corroborar que a pesar de que existen muchas organizaciones barriales en el sitio, no están cumpliendo el rol o su función para lograr el progreso y mejorar la calidad de vida de las personas mediante la ejecución de obras trabajando coordinadamente con las autoridades competentes del GADM de Arenillas. Por esta razón, el objetivo general de la investigación se centra en Determinar la incidencia la organización social en el desarrollo comunitario del Sitio San Vicente del Jobo. Así mismo, el trabajo de investigación se fundamenta en la Teoría Sociológica Estructural Funcionalismo de Emeli Durkheim puesto que, las organizaciones sociales se relacionan con la sociedad y sus estructuras que funciona gracias a los roles que desempeña cada individuo desde su respetivo status, por ende, lograr el progreso y desarrollo social. El enfoque metodológico aplicado en la investigación es el cuantitativo la cual contribuyo a un trabajo más sistematizado en la obtención de información verídica, así mismo se recopilo información mediante la técnica de la encuesta con el fin de explicar y analizar los datos obtenidos, mismo que facilito una interpretación más precisa y clara. En base a los resultados obtenidos se puede manifestar que existen, problemas sociales internos en el sitio, las organizaciones sociales existentes están debilitadas y no están cumpliendo su función correctamente, de acuerdo con los datos reflejan que existen intereses individuales en la directiva y son de carácter lucrativos y económicos y su aceptación de la misma es bajo, además que la calidad de vida los habitantes es bajo y existen diferencias ideológicas por partidos y movimientos políticos en tiempos de campañas, todos estos problemas están incidiendo y obstaculizando de manera negativa en el desarrollo comunitario del sitio y afectando a la calidad de vida de los habitantes retrasando la ejecución de obras en beneficio de la población, en función a lo mencionado la problemática objeto de estudio debe ser atendida inmediatamente desde el fortalecimiento de la comunidad y liderazgo , empoderándola y comprometiendo tanto a los moradores como a las autoridades cantonales con la finalidad de lograr el bienestar colectivo.
Keywords: ORGANIZACION SOCIAL; LIDERAZGO; INCIDENCIA; FORTALECIMIENTO COMUNITARIO